Research Collaboration Network Among the Local Academics: A Review - Daud, Suriana Che; Ismail, Saidatul Akmar; Yahaya, Haliza; Idris, Sufy Rabea Adawiya; Ramsi, Mohd Faizal Mohd (Journal of Informatics and Mathematical Sciences, 2017)
This paper is a conceptual paper on research collaboration network among the local academics. The academicians collaborate and network among themselves for several reasons. The literature review indicated that the reasons were to access to expertise in the area of interest, to access to instruments, andcross-fertilization across disciplines are among the factors for individual research collaboration. A research is proposed in order to identify the factors that contribute to the collaboration of local researchers since there is no study has been done in the context of the study. Social analysis network will be used as a guide to the proposed study to determine the level of relationship between authors.